Dissecting Diversity: Experiences of migrant and minority student populations in SETU Carlow - Nolan, Sandra (STER, 2024)
This paper will outline findings from a study that examined the experiences of education inclusion and exclusion for migrant and minority ethnic students at SETU Carlow. The study sought to answer whether or not access to third level education for migrant and ethnic minority students in SETU Carlow can be facilitated through inclusive pedagogies. The paper will highlight research findings under the theme ‘Diversity’ – one of four themes explored in the study. Other themes from this study include ‘Inclusion’ and ‘Belonging’, and are discussed in a forthcoming paper (Nolan, 2024). The methodological design is also described here, along with the idea of researcher’s positionality, and the role of HEIs around the theme selected. To protect the anonymity of research participants, the identifier ‘Participant X’ is used to indicate focus group responses, and ‘Survey Respondent’ is used to indicate survey questionnaire responses. This study was approved by the ethical committee of SETU and conducted in line with all ethical procedures and requirements. Under the theme ‘Diversity’, findings are discussed as Macro-level Diversity – referring to the institution as a whole; Meso-level Diversity – referring to the general climate of the institution; and Micro-level Diversity – referring to the individual student experience of diversity. In line with the work of Tan (2019) this research study understands diversity in education as: “The presence of differences within a given setting. This may include gender, race, ethnicity, religion, nationality, sexual orientation, place of practice, and practice type.” Incorporating a sociological perspective of the term diversity regarding educational environments, this research study demonstrated a positive relationship between ethnocultural diversity and access to education. This paper argues that there must be closer attention given to understanding how policies on diversity are best acted on in the interest of the student experience.
Keywords: Intercultural Education; Access to Education; Minority students; Belonging; Diversity